Assessing the Contribution of Seasonality, Tides, and Microbial Processing to Dissolved Organic Matter Composition Variability in a Southeastern U.S. Estuary - Martineac, Rachel P.; Vorobev, Alexey V.; Moran, Mary Ann; Medeiros, Patricia M. (Frontiers in Marine Science, 2021)
Uncovering which biogeochemical processes have a critical role controlling dissolved organic matter (DOM) compositional changes in complex estuarine environments remains a challenge. In this context, the aim of this study is to characterize the dominant patterns of variability modifying the DOM composition in an estuary off the Southeastern U.S. We collected water samples during three seasons (July and October 2014 and April 2015) at both high and low tides and conducted short- (1 day) and long-term (60 days) dark incubations. Samples were analyzed for bulk DOC concentration, and optical (CDOM) and molecular (FT-ICR MS) compositions and bacterial cells were collected for metatranscriptomics. Results show that the dominant pattern of variability in DOM composition occurs at seasonal scales, likely associated with the seasonality of river discharge. After seasonal variations, long-term biodegradation was found to be comparatively more important in the fall, while tidal variability was the second most important factor correlated to DOM composition in spring, when the freshwater content in the estuary was high. Over shorter time scales, however, the influence of microbial processing was small. Microbial data revealed a similar pattern, with variability in gene expression occurring primarily at the seasonal scale and tidal influence being of secondary importance. Our analyses suggest that future changes in the seasonal delivery of freshwater to this system have the potential to significantly impact DOM composition. Changes in residence time may also be important, helping control the relative contribution of tides and long-term biodegradation to DOM compositional changes in the estuary.